2021
DOI: 10.1038/s41598-021-85975-z
|View full text |Cite
|
Sign up to set email alerts
|

A high-efficiency Klebsiella variicola H12-CMC-FeS@biochar for chromium removal from aqueous solution

Abstract: In polluted groundwater, surface water, and industrial sites, chromium is found as one of the most common heavy metals, and one of the 20 main pollutants in China, which poses a great threat to the ecological environment and human health. Combining biological and chemical materials to treat groundwater contaminated by heavy metals is a promising restoration technology. In this research, Klebsiella variicola H12 (abbreviated as K. variicola) was found to have Cr(VI) reduction ability. A high-efficiency Klebsiel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…In contrast, raw biochar contained the least amount of carbon. Literature reported the correlation of C content with the dye sequestration capacity of the carbonaceous particles (Yu et al, 2021) and found better efficiency with high C content (Xiong et al, 2013). The higher MO sorption by the activated biochar prepared at 500°C in our study is compatible with the remarks suggested by (Xiong et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, raw biochar contained the least amount of carbon. Literature reported the correlation of C content with the dye sequestration capacity of the carbonaceous particles (Yu et al, 2021) and found better efficiency with high C content (Xiong et al, 2013). The higher MO sorption by the activated biochar prepared at 500°C in our study is compatible with the remarks suggested by (Xiong et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…Promote growth on plants (Gupta et al, 2019). At present, Klebsiella variicola H12-CM-Fes@ (Yu et al, 2021a) and microbacterium Testaceum B-HS2 (Amina et al, 2019), Sporosarcina Saromensis W5 (Huang et al, 2021) and Bacillus sp. CRB-B1 (Tan et al, 2020) have been identified with high efficiency in removing chromium.…”
Section: Inductionmentioning
confidence: 99%
“…Then they were divided into two parts. In the rst part, the samples were xed, dehydrated, and dried by glutaraldehyde, and the microstructure and element distribution of the mycelia were characterized via SEM and energy dispersive spectroscopy (EDS) (Yu et al 2021). After freeze-drying, the other samples were used to analyze the element content of thalli.…”
Section: Analysis Of the Nuclide Enrichment Characteristics Of The Fungimentioning
confidence: 99%